EFFECTS OF FORMATIVE ASSESSMENT ON COMPETENCY DEVELOPMENT - Musurmonova Saodat (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: The purpose of this study is to explore how formative assessment impacts the development of competencies in science and technology. Assessment plays a vital role in bridging instruction and learning. Although it appears in multiple formats, its primary role is to determine how much knowledge and understanding students have gained during a lesson or series of lessons. William (2010) emphasizes that assessment is a key element of successful teaching, as it is the only way to confirm whether students have comprehended the material. Formative assessment, in particular, is an ongoing process that occurs alongside learning, aiming to track and enhance student performance. Hattie (2012) highlights that this type of assessment responds to individual student needs and significantly contributes to educational progress. Despite strong support for the benefits of formative assessment, certain aspects still require deeper research.